Compulsory Execution under the Check in the UAE Law - Mariam Ahmed AL sandal, (Journal of Legal Sciences, 2024)
The study dealt with the issue of Compulsory Execution under the check in UAE law, so the legislator considered it an executive document in some cases, when the legally prescribed controls for that are available.The UAE legislator did not explicitly specify whether the cases of considering a check as an executive document are exclusive or not, and did not clarify the conditions for considering a check as an executive document and the procedural rules followed, especially since they came in two different laws, namely the Commercial Transactions Law and the Civil Procedure Law.We addressed the topic by explaining the cases of considering a check as an executive document, then the conditions for considering a check as an executive document, then the procedural rules for considering a check as an executive document.The most important results of the study: The Authority for the Unification of Federal and Local Judicial Principles added a case to the cases of considering a check as an executive document stipulated by law. The most important recommendations of the study: The need to remove the conflict between the text of Article 667 and Article 684 of Federal Decree Law No. 50 of 2022.